Assessment of Plasma-Endogenous Opioid Neuropeptide Levels and Psychometric Properties of Non-Suicidal Self-Injury in Adolescents - Cakin Memik, Nursu; Hunc, Fatih; Kalayci, Seyma; Demir, Necmettin; Senturk, Elif; Yildiz Gundogdu, Ozlem; Ozlen Dillioglugil, Meltem (Archives of suicide research, 2023)
Non-suicidal self-injury (NSSI) is one of the most common mental health problems and growing public-health issues, coupled with a significant population-level burden among adolescents in both developed and developing countries. We aimed to assess the role of endogenous opioid system-emotion regulation circuitry in NSSI through measurement of plasma beta-endorphin (β-EP), met-enkephalin (MENK) levels, and determination of psychometric features of Turkish adolescent subjects. In this research, we measured plasma β-EP and MENK levels of 49 adolescents with NSSI and 39 control subjects without NSSI between the ages of 12-18 years. All adolescent subjects were observed in the outpatient clinic, and their clinical and sociodemographic characteristics were examined. All subjects were assessed using the Brief Symptom Inventory (BSI) and Inventory of Statements About Self Injury (ISAS). Plasma β-EP levels were statistically lower in adolescents with NSSI than control group, whereas there was no statistically significant difference in MENK levels. β-EP levels showed a negative correlation with depression severity. The data obtained from BSI and ISAS were not found to be associated with both β-EP and MENK levels, while subscale scores exhibited versatile correlations. Our findings supported the salient role of β-EP in NSSI behavior. Also, decreased plasma β-EP could be assessed as a reliable indicator for NSSI. However, it is possible that measurement of basal plasma levels of neuropeptides might also bring many confounders and could cause bias. Therefore, repeated measurements of plasma-endogenous opioid neuropeptides in a time-dependent manner-concomitant to engage of NSSI behavior-might give more reliable results.